Effects of water matrices on the degradation of naproxen by reactive radicals in the UV/peracetic acid process. (1st March 2019) - Chen, Siao; Cai, Meiquan; Liu, Yongze; Zhang, Liqiu; Feng, Li
Abstract: The UV/peracetic acid (UV/PAA) process as a novel advanced oxidation process has been reported to produce carbon-centered radicals (RC) for Naproxen (NAP) degradation, which is a representative of naphthyl structure substances. Real water matrices, such as carbonate and bicarbonate ions (CO3 2− /HCO3 − ), humic acid (HA), and chloride ion (Cl − ), may react with these reactive radicals and change their contributions to NAP degradation. The results showed that RC contributed 60.8% and OH contributed 39.2% to NAP degradation in pure water by a competition method. CO3 2− /HCO3 − (0–20 mM) showed minimal effect on NAP degradation in the UV/PAA process, meanwhile, it has observable inhibition effect on NAP degradation in the UV/H2 O2 process (mainly of OH) and minimal effect in the UV/PAA process with tert-butanol (TBA) (mainly of RC). Results suggested that CO3 2− /HCO3 − could react with OH yielding CO3 - with low reactivity to NAP, CO3 - could further react with PAA to produce RC. This speculation was confirmed by the increased contribution of RC to NAP degradation with the increase of CO3 2− /HCO3 − concentration through the competition method. HA (0–5 mg/L) had a higher scavenging capacity for RC than OH because HA with naphthyl structure was likely to be attacked by RC. Cl − (0–200 mM) had little effect on NAP degradation in the UV/PAA and UV/H2 O2 processes, while exerted an observable inhibition on NAP degradation in the UV/PAA process with TBA. This finding suggested that Cl − could react with RC to produce Cl, which could further convert into HOCl -, and then excess OH was formed. The new knowledge on the conversion of reactive radicals obtained in this study provides an important basis for facilitating further research on the UV/PAA advanced oxidation. Graphical abstract: Highlights: Contribution of reactive radicals to Naproxen degradation was determined. CO3 2− /HCO3 − can converse OH to carbon-centered radicals in the UV/PAA process. Cl − can converse carbon-centered radicals to OH in the UV/PAA process. Humic acid showed higher scavenging rate to carbon-centered radicals than OH. The influencing mechanism of water matrices on Naproxen degradation was proposed.